TRANSFORMASI KESADARAN KEAGAMAAN MAHASISWA TEKNIK MESIN MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI KAMPUS POLINEMA PSDKU KEDIRI - Muhammad Arifin; Suko Susilo; Muhammad Yunus (STKIP Subang, 2025)
This study aims to identify the transformation of religious awareness among first-semester students of the Mechhanical engineering Study Program at Polinema PSDKU Kediri after participating in Islamic Religious Education courses. The research employs a descriptive qualitative approach, using interviews as the primary data source and literature riview as the secondary data source. Data were collected through interviews with several first-semester Mechanical Engineering students at Polinema PSDKU Kediri, as well as through analysis of literature related to the throry of transformative learning developed by Jack Mezirow. The results of this study indicate that the Islamis Rlegious Education cours plays a significant role in enhancing the religious awareness of mechanical engineering student. This enhancement is evident in three main aspects: 1) Cognitive, the development of new understanding related to moral values that are relevant to the field of engineering, monotheism, and worship. 2) Affective, an increase in commitment to religious practices and moral responsibility. 3) Behavioral, consistency in performing religious obligations and integrating Islamic values into academic and practical activities. These findings further support Mezirow’s theory that reflective learning can dismantle old paradigms and lead to the development of new, more meaningful perspectives. Thus, The Islamic Religious Education course has proven to play an essential role in fostering the integration of faith, knowledge, and professionalism among engineering students.